a(a-b+2)-6b(b+1) 因式分解
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 23:49:10
a(a-b+2)-6b(b+1)因式分解a(a-b+2)-6b(b+1)因式分解a(a-b+2)-6b(b+1)因式分解a(a-b+2)-6b(b+1)=a^2-ab+2a-6b^2-6b=a^2-a
a(a-b+2)-6b(b+1) 因式分解
a(a-b+2)-6b(b+1) 因式分解
a(a-b+2)-6b(b+1) 因式分解
a(a-b+2)-6b(b+1)
=a^2-ab+2a-6b^2-6b
=a^2-ab-6b^2+2(a-3b)
=(a+2b)(a-3b)+2(a-3b)
=(a-3b)(a+2b+2)
a(a-b+2)-6b(b+1)分解因式
(a+b)^2-4(a+b+1) 这是一道因式分解题,Thanks
分解因式;(a+b)^2+(a+b)-6
分解因式:(a+b)^2+(a+b)-6
分解因式:(a+b)^2+(a+b)-6
9+6【a+b】+【a+b】^2分解因式
(a+b)^2--4(a+b--1)分解因式
(a+b)*(a+b-2)+1怎么分解因式
(a-b-1)(a-b)-2 分解因式
分解因式 (a-b)(a-b-2)+1
a^-b^+6b-9分解因式,
分解因式a-b×b
分解因式 a^2(a-b)+b^2(b-2)
分解因式:(a+b)(a+2b)+b^2/4
a(a-2b)+b(a-2b)分解因式 (a-2b)(a+b)
4a^2-b^2+2b+1 分解因式
分解因式:4a^2-b^2+2b-1
分解因式 a^2-b^2-2b-1